Out-of-hospital births and the experiences of emergency ambulance clinicians and birthing parents: a scoping review protocol. Issue 5 (25th May 2022) - Hill, Michella; Miles, Alecka; Flanagan, Belinda; Mills, Brennen; Hopper, Luke
Abstract : Introduction: Emergency ambulance clinicians attend a wide range of prehospital emergencies, including out-of-hospital births (OOHBs). Intrapartum care comprises approximately 0.05% of emergency medical services' caseload, with only 10% of intrapartum cases progressing to birth in emergency ambulance clinician care. However, this low exposure rate potentially allows obstetric clinical skills and knowledge to decay, which may impact on patient care. Additionally, unplanned OOHBs are known to have a higher incidence of complications and adverse outcomes than their counterparts born in hospital, such as postpartum haemorrhage or hypothermia. This scoping review will explore OOHBs and associated complications in emergency ambulance clinician care, investigate birth parent, significant partner and clinician experiences regarding OOHBs, and consider barriers and challenges to optimal patient care, to identify future research opportunities and associated knowledge gaps for this patient cohort. Methods and analysis: This scoping review will follow the nine-step methodological framework suggested by the Joanna Briggs Institute and use the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. Five electronic databases (MEDLINE via EBSCO, CINAHL, Embase, Web of Science and Wiley Online) will be searched to identify articles for inclusion. The 'participant, concept, context' criteria will be used to identify suitable search words regarding OOHBs in emergency ambulance clinician care. The review will include peer-reviewed and preprint literature. Two reviewers will independently assess articles based on title and abstract for inclusion in the review. Data will be charted using a data extraction tool for consistency and provide a succinct descriptive summary of the results. Ethics and dissemination: This study does not require ethical review as all the information obtained will come from publicly available resources. Results will be disseminated via a peer-reviewed publication. This scoping review is preregistered with the Open Science Framework (https://osf.io/ta35q ).